Carbon management, local governance and community engagement. Issue 4 (August 2012) - Peters, Michael; Fudge, Shane; Hoffman, Steven M; High-Pippert, Angela
This article examines the role of communities in carbon management as it relates to both climate change and energy policy at the local level and as a seedbed for grassroots activity. The article considers some of the implications of recent policy developments, particularly the ways in which the 'lines of responsibility' are now being drawn at the local level. Drawing upon in-depth interviews with local authorities in the UK and the USA, the article examines the political distinctions that are evident between the two situations and the ramifications of these for practical community engagement in carbon management at the local level. Community engagement is likely to be central to the delivery of CO2 reductions, but evidence so far points to a series of challenges that will require a greater emphasis on partnership working between community groups and formal decision-making bodies.